Development of impulsivity and risk‐seeking: Implications for the dimensionality and stability of self‐control*. Issue 3 (11th June 2019) - Forrest, Walter; Hay, Carter; Widdowson, Alex O.; Rocque, Michael
Abstract: In Gottfredson and Hirschi's self‐control theory, introduced in 1990, they contend that self‐control is a unidimensional construct that develops early in childhood and remains stable throughout the life span. According to findings reported in recent research, however, these arguments are now being challenged, with scholars pointing to ways in which self‐control may be multidimensional in nature and may change beyond the period of alleged stabilization. In this study, we draw on Steinberg's dual systems model, introduced in 2008, to consider this issue further. We examine that model's two key elements of low self‐control—risk‐seeking and impulsivity—to determine whether they are empirically distinguishable from one another and have differing developmental trajectories from childhood to early adulthood. We also consider the consequences of changes in risk‐seeking and impulsivity for within‐individual changes in crime. We examine these issues with data from the National Longitudinal Survey of Youth 1979 (NLSY79) for individuals from 10 to 30 years old. The results of our analyses show support for a multidimensional and dynamic conception of self‐control—from age 10 to age 30, risk‐seeking and impulsivity are empirically distinct and develop in divergent ways that are consistent with the dual systems model. Changes in risk‐seeking and impulsivity also affect changes in crime, but their effects vary with age and changes in the other element. We discuss these findings and their implications for self‐control and the development of life‐course criminology.